Exposing Patriarchal Bias in the Interpretation of Q.S An-Nisa 1 and 34: A Study of Amina Wadud's Thoughts for Inclusive Islam - A Aidil; Cima Ghoziah; Muhammad Ahsanul Aziz; Firman Azali; Muhammad Faras Heztio (QiST: Journal of Quran and Tafseer Studies, 2025)
Verses 1 and 34 of Surah An-Nisa are pivotal Quranic texts frequently referenced in discussions about gender relations. Traditionally, interpretations of these verses have been shaped by patriarchal views, largely due to male dominated scholarly traditions. Amina Wadud, a noted Muslim feminist scholar, introduces a hermeneutic feminist perspective that challenges biased readings disadvantaging women. This study critically examines Wadud's interpretative approach to these verses and assesses her role in fostering a more equitable, contextual, and inclusive understanding of Islamic scripture. Employing a qualitative method based on literature review and descriptive analytical analysis, this research highlights Wadud's emphasis on historical context, social realities, and female experiences in Quranic interpretation. The findings reveal that while Wadud upholds the Quran's authority, she contests traditional readings that restrict women's rights and roles unjustly. Her work expands the discourse on gender equity within Islam and offers valuable insights for progressive Islamic thought, especially relevant in Indonesia's ongoing dialogue on gender equality. This study underlines the necessity of reinterpreting sacred texts through compassionate and context-aware lenses to ensure Islamic principles genuinely promote justice for all, including women.